Cutting red tape: Legal and institutional tools to promote SMEs - Tina Sever; Dejan Ravšelj; Aleksander Aristovnik; Polonca Kovač (DANUBE: Law, Economics and Social Issues Review, 2020)
The pursuit of global competitiveness requires a complex system of measures that enable the promotion of business. Yet this goal is strongly hindered by interdisciplinary (legal, economic, managerial, IT) red tape programs in both national and supranational frameworks. The aim of the paper is to enhance the understanding of red tape by identifying key sector-specific problems in administrative areas that are crucial for SMEs and offer suggestions for improvement. The paper explores measures related to red tape in the Slovenian and European contexts based on the understanding that transparent regulation with efficient procedures is a precondition for a business-friendly environment that attracts investments. The research is based on a combination of empirical methods applied to a base of over 900 surveys collected from Slovenian SMEs in 2016 and 2017. The results show that entrepreneurs see the greatest administrative burdens in the area of accounting and financial reports, especially the number of the documents needed, the time needed to perform a procedure, and the need for outsourcing.
Keywords: 330; Red Tape Reduction; Administrative Burden; Doing Business; SMEs; Stakeholders' Perception; Slovenia